Application of quality tools in a tire factory: a case study for reducing rework due to tread shortage - Silva, Natália Macêdo e; Oliveira, Willma Bastos Ribeiro; Santos, Maylane Neres Costa; Santos, André de Mendonça; Damm, Djoille Denner (Brazilian Journal of Production Engineering, 2025)
This research aims to analyze the tire manufacturing process and investigate the possible causes of the high rework rate related to “tread shortage”. To identify the root causes, a systematic method was conducted with the help of quality tools: 5 Why; Ishikawa Diagram; Brainstorming; and 5W2H. The analysis included the collection of historical rework data and meetings with a multidisciplinary team. As a result, the number of defective tires was reduced by 50%, and the technical index went from 0.35% to the target of 0.28%. This improvement directly reflected in increased efficiency, cost reduction and increased productivity of the plant. The main causes of the problem were identified and based on them, corrective and preventive actions were taken to mitigate the impacts of rework on the production flow.
Keywords: tires; rework; quality tools; rubber shortage